1999
DOI: 10.1271/bbb.63.1569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Probiotic on the Lipid Metabolism of Cocks Fed on a Cholesterol-enriched Diet

Abstract: The effects of a probiotic (a mixture of Bacillus, Lactobacillus, Streptococcus, Clostridium, Saccharomyces and Candida) on the lipid metabolism, and caecal flora and metabolites of cocks were studied. The cholesterol level of the liver and serum was significantly decreased in the cocks fed on the cholesterol-enriched diet containing the probiotic. The distribution and frequency of occurrence of flora, and the chemical characteristics of the metabolites in the caecal content of the cocks were also affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…C. butyricum tended to reduce serum concentrations of TG and TC in the present study. Limited research focusing on the effect of probiotics on lipid metabolism of chicks indicated that the serum level of cholesterol was significantly decreased by adding a mixture of Bacillus, Lactobacillus, Streptococcus, Clostridium, Saccharomyces and Candida into the diet (Endo et al, 1999). Previous studies reported that a fish oil diet significantly decreased serum levels of cholesterol and TG Castillo et al, 2000), while fish oil reduced serum TC levels, but not cholesterol, in our study.…”
Section: Discussionsupporting
confidence: 44%
“…C. butyricum tended to reduce serum concentrations of TG and TC in the present study. Limited research focusing on the effect of probiotics on lipid metabolism of chicks indicated that the serum level of cholesterol was significantly decreased by adding a mixture of Bacillus, Lactobacillus, Streptococcus, Clostridium, Saccharomyces and Candida into the diet (Endo et al, 1999). Previous studies reported that a fish oil diet significantly decreased serum levels of cholesterol and TG Castillo et al, 2000), while fish oil reduced serum TC levels, but not cholesterol, in our study.…”
Section: Discussionsupporting
confidence: 44%
“…The result of increased synthesis of these acids reduces the concentration of cholesterol. After adding probiotics to the diet, the cholesterol concentrations in the liver and blood serum were significantly lower in cockerels (Endo et al, 1999) and in rats (Hosono, 2000(Hosono, , 2001. According to Kurtoglu et al (2004), supplementation of 250, 500 and 750 mg/kg probiotic increased egg production, reduced the number of cracked eggs, and decreased the egg yolk and serum cholesterol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The probiotics treatment had higher Bacilli population than control in hay feeding (Table 5). Endo et al . (1999) reported an increase of Bacilli in the caecal contents of cocks supplemented by a mixture of probiotics, Bacilli , Lactobacilli , Streptococci , Saccharomyceae and Candidae .…”
Section: Discussionmentioning
confidence: 99%